Kepuasan pelanggan sebagai mediasi relationship marketing dan penetapan harga terhadap loyalitas pelanggan - wulandari; Sudirman, M.; Astuti, Siti (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
This study aims to examine, examine, and analyze customer satisfaction as a mediation of relationship marketing and pricing on multi-level marketing customer loyalty in Kab. Tangerang. The rise of multi-level marketing business competition today, companies must maintain and fulfill customer desires. Therefore, the marketing strategy recognizes the concept of relationship marketing and pricing. This research method uses descriptive quantitative. The sample technique used is proportionate stratified random sampling. The number of respondents is 100. The data analysis technique used is path analysis to determine the direct and indirect effects. The results of data analysis show that customer satisfaction variables cannot mediate relationship marketing and pricing on multi-level marketing customer loyalty in Kab. Tangerang, because the value of indirect influence is smaller than the value of direct influence